2010
DOI: 10.1007/s11695-010-0213-0
|View full text |Cite
|
Sign up to set email alerts
|

Does Surgically Induced Weight Loss Improve Daytime Sleepiness?

Abstract: Morbid obesity is associated with excessive daytime sleepiness and reduced health-related quality of life. We prospectively evaluated the pre- and postoperative responses of bariatric surgery recipients with the Epworth Sleepiness Scale (ESS) and the Short Form-12. Participants (n = 223; 79% women) with a mean body mass index (BMI) and ESS of 44.8 ± 7.9 kg/m(2) and 7.9 ± 4.5, respectively, received a vertical gastrectomy (76%) or Roux-en-Y gastric bypass (12%). Preoperatively, 30% of patients complained of exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 81 publications
1
11
1
Order By: Relevance
“…The majority of the subjects in the present study showed an improvement in excessive daytime sleepiness after surgery, in agreement with previous investigations [22][23][24]. It has been suggested that the decrease in hypersomnolence after bariatric surgery may be related to an improvement in nocturnal sleep, secondary to the reduction in OSA, as mentioned above, although other factors, such as a reduction of metabolic and inflammatory abnormalities, could also play a role [9,25,26].…”
Section: Discussionsupporting
confidence: 93%
“…The majority of the subjects in the present study showed an improvement in excessive daytime sleepiness after surgery, in agreement with previous investigations [22][23][24]. It has been suggested that the decrease in hypersomnolence after bariatric surgery may be related to an improvement in nocturnal sleep, secondary to the reduction in OSA, as mentioned above, although other factors, such as a reduction of metabolic and inflammatory abnormalities, could also play a role [9,25,26].…”
Section: Discussionsupporting
confidence: 93%
“…Such sleepiness is routinely associated with obesity in otherwise healthy individuals [39-41], and weight management strategies are a common treatment approach in the general population [42]. Our results suggest that weight reduction in HL survivors may not only improve physical functioning but also excessive daytime sleepiness.…”
Section: Discussionmentioning
confidence: 75%
“…In a previous study, Holty et al [ 41 ] described significant reductions in mean ESS scores 24 months after bariatric surgery; however, in that study the operation of choice was vertical gastrectomy and Roux-en-Y gastric bypass. In the current study, the authors found that the 6-month post-operative mean ESS scores after sleeve gastrectomy were significantly reduced from 9.0 ± 4.6 to 3.5 ± 2.2 ( P < 0.001).…”
Section: Discussionmentioning
confidence: 98%